Fetishized hijab and resilient Muslim women: Representations of the veil in Leila Aboulela’s Minaret and in Shelina Janmohamed’s Love in a Headscarf - Hasan, Md. Mahmudul (2014)
In the post-9/11 and 7/7 era of xenophobia, vulnerability and vicissitudes, the Muslim diaspora in the West is at the center of contestations about identities and racked with somewhat unacknowledged exilic anxieties. However, as they experience “double colonization” by patriarchy and imperialism in their country of origin, diasporic Muslim women suffer dual oppressions of racism/Islamophobia and sexism from within their communities in the metropolis. An added vulnerability of diasporic Muslim women is the palpable and distinguishable visibility of the hijab many of them wear and become subject to collective stigmatization. While the Muslim woman’s headscarf is an unmistakable target for attacks from right-wing forces, it also provokes unease and invites disapproval from a section of diasporic Muslims. What is more, despite the sartorial freedom to wear revealing dresses, which is largely absent in many Muslim-majority countries but which the culturally-different host country offers, many diasporic Muslim women show staunch resilience and choose to wear the hijab even though they live in a predominantly Islamophobic society. These women also use the third space of diaspora to engage confidently in the reinterpretation of the Islamic texts and thus reclaim an identity which liberates them from the culturally enacted practices of their country of origin. Based on these theoretical premises, my paper will analyze the representation of hijab and of hijab-wearing women in Leila Aboulela’s Minaret (2005) and in Shelina Janmohamed’s Love in a Headscarf (2009) and will discuss the resilience the heroines of these works show with regard to adhering to the Islamic dress code.